EFEK MODIFIKASI PERMUKAAN KARBON AKTIF MONOLIT TERHADAP SIFAT FISIS DAN ELEKTROKIMIA SEL SUPERKAPASITOR - Yanti, Sri; Taer, Erman; ', Sugianto (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Surface modification of activated carbon monolith electrode for a supercapacitor cell from rubber wood has successfully been made by two activation methods. Physical activation was perfomed using CO2 gas at a temperature of 800oC, and chemical activation used 3 M KOH and 3 M NaOH as activation agents. This study used two kinds of activated agents, namely COK for KOH activated agent and CON for NaOH activated agent. Both activation methods yielded different physical and electrochemical properties. The physical properties that were analyzed were density , surface morphology, and BET surface area, whereas the electrochemical properties were specific capacitance, specific energy, and specific power. N2 gas isothermal adsorption showed a BET surface area of 577.52 m2g-1 and 441.45 m2g-1. Meanwhile, the electrochemical properties obtained of sample were the specific capacitance values of 103.65 Fg-1 and 83.45 Fg-1for CON and COK, respectively . Based on all obtained data and their analysis, it was concluded that KOH activators resulted the electrochemical properties better compared tothose of NaOH activators.